Компенсація моральної шкоди, завданої закладам вищої освіти внаслідок війни - Попова, С. О.; Popova, S. O.; Глазкова, В. О.; Hlazkova, V. O.; Софія Попова (Право і безпека. - 2025. - № 1 (96). - С. 150-162, 2025)
Статтю присвячено дослідженню можливостей звернення закладів вищої освіти щодо компенсації моральної шкоди, завданої внаслідок війни. Проаналізовано правові засади діяльності закладів вищої освіти. Зокрема, зазначено, що до їхніх основних завдань належить забезпечення здобуття особами вищої освіти відповідного ступеня за обраними спеціальностями шляхом провадження освітньої діяльності на високому рівні. Зроблено висновок, що через збройну агресію рф проти України повноцінне виконання цього завдання є неможливим. Водночас вказано, що воєнні дії порушують особисті немайнові права юридичної особи – закладу вищої освіти. Визначено, що порушення права на недоторканність ділової репутації є підставою для компенсації моральної шкоди юридичним особам. Проаналізовано, як поняття ділової репутації тлумачиться в законодавстві України та правовій доктрині. Сформульовано авторське визначення ділової репутації закладу вищої освіти як оцінки якості провадження наукової, науково-технічної, інноваційної та/або методичної діяльності педагогічних, науково-педагогічних та наукових працівників установи, що має ліцензію на провадження освітньої діяльності на відповідних рівнях вищої освіти. Розглянуто проблеми, з якими стикаються заклади вищої освіти через війну і які призводять до погіршення їхньої ділової репутації. Доведено, що внутрішній клімат в організації має істотне значення для формування позитивної ділової репутації закладу вищої освіти. Це зумовлено наявним взаємозв’язком між можливістю здійснення освітньої діяльності науково-педагогічними працівниками та їхнім відчуттям безпеки, мотивації та сприятливими умовами праці. Важливим чинником є також здатність здобувачів освіти отримувати якісні освітні послуги й демонструвати високі результати навчання. Звернено увагу, що нині в українському законодавстві відсутній спеціальний механізм компенсації моральної шкоди, спричиненої війною, для юридичних осіб. Єдиним загальноприйнятим способом захисту є звернення з позовом до суду. Водночас визнання самого факту можливості компенсації моральної шкоди закладами вищої освіти у зв’язку з війною є важливим кроком до подолання наявних проблем. У підсумку зазначено, що універсальної моделі визначення розміру моральної шкоди за завдані порушення не існує. Єдина формула розрахунку відсутня, а навіть орієнтовні критерії встановлюються на підставі досвіду та практики розгляду судами справ у подібних правовідносинах.

The article is devoted to the study of the possibilities for higher education institutions to apply for compensation for moral damage caused by war. The legal framework of higher education institutions is analysed. In particular, it is noted that their main objectives are to ensure that persons obtaining higher education receive the appropriate degree in their chosen specialties through high-level educational activities. It is concluded that due to the armed aggression of the Russian Federation against Ukraine, it is impossible to fulfil this task in full. At the same time, it is noted that military actions violate the personal non-property rights of a legal entity such as a higher education institution. It is determined that the violation of the right to inviolability of business reputation is the basis for compensation for non-pecuniary damage to legal entities. The concept of business reputation is analysed in Ukrainian legislation and legal doctrine. The author's definition of the business reputation of a higher education institution is formulated as an assessment of the quality of scientific, scientific and technical, innovative and/or methodological activities of pedagogical, scientific and pedagogical and scientific employees of an institution licensed to conduct educational activities at the relevant levels of higher education. The article considers the problems faced by higher education institutions due to the war and which lead to a deterioration in their business reputation, It is proved that the internal climate in an organisation is essential for the formation of a positive business reputation of a higher education institution. This is due to the existing relationship between the ability of academic staff to carry out educational activities and their sense of security, motivation and favourable working conditions. An important factor is also the ability of students to receive quality educational services and demonstrate high learning outcomes. The attention is drawn to the fact that at present, Ukrainian legislation does not provide for a special mechanism of compensation for moral damage caused by the war for legal entities. The only generally accepted method of protection is to file a lawsuit in court. At the same time, the recognition of the very fact that higher education institutions can compensate for moral damage caused by the war is an important step towards overcoming the existing problems. In conclusion, it is noted that there is no universal model for determining the amount of nonpecuniary damage for violations. There is no single formula for calculation, and even indicative criteria are established based on the experience and practice of courts in considering cases in similar legal relations.
Compensation for moral damage caused to higher education institutions due to the war
Keywords: відшкодування шкоди; моральна (немайнова) шкода; відповідальність; освітня діяльність; воєнний стан; цивільні правовідносини; особисті немайнові права; compensation for damages; moral (non-pecuniary) damage; liability; educational activities; martial law; civil legal relations; personal non-property rights